AUTOMATIC ENERGY BILL SHOWING ON SINGLE PHASE ENERGY METER - Rupali T. Bansode; Dhanraj D. Daphale; Pallavi M.Bile (International Journal of Innovations in Engineering Research and Technology, 2022)
This paper presents the way of billing which shows that there is no need of any human being for billing purpose. It can be done automatically with the help of microcontroller program. In this paper a cost effective novel single phase digital energy meter is developed with the help of Microcontroller which is capable of calculating true value of active, reactive, apparent power, power factor and energy consumed. The designed meter is simple, portable and easily reconfigurable according to specific need. The parameters calculated are transmitted to the billing on energy meter display. In this for the we communicate to eliminating the need for the utility personnel calculate meter reading without any manual calculations. This data gets logged in and is used for generating bills and can also be used for analysis in the order to improve the power quality and understand the load and use pattern. The detailed bill generated easily and show to display of single phase energy meter.